Iura novit arbiter na arbitragem internacional: origem, limites e aplicação prática - Silva, Caio Lopes da (2024)
This study addresses the principle of iura novit arbiter, exploring its origins, limits, and practical applications in the contemporary legal and arbitration contexts. The dissertation examines contemporary criticisms and debates regarding the extent of the principle's applicability by arbitrators in arbitral proceedings, considering the duties of arbitrators and procedural principles. The research proposes a thorough reflection on how this principle can coexist harmoniously with due process and the effective participation of parties in the judicial process. The practical applications of iura novit arbiter are explored through representative case studies in key jurisdictions hosting arbitrations, highlighting situations where the principle plays a crucial role in resolving legal disputes. Finally, this thesis offers a comprehensive analysis of iura novit arbiter, from its origins to practical implications, contributing to a deep understanding of this principle and its optimal application. The research aims to provide valuable insights for academics, legal professionals, and arbitrators